First Italian birth after cryopreserved ovarian tissue transplantation in a patient affected by non-Hodgkin's lymphoma. (4th December 2018) - Fabbri, Raffaella; Macciocca, Maria; Vicenti, Rossella; Paradisi, Roberto; Rossi, Stefani; Sabattini, Elena; Gazzola, Anna; Seracchioli, Renato
This case report describes the first Italian live birth obtained by cryopreserved ovarian tissue transplantation in a woman affected by non-Hodgkin's lymphoma. Before anticancer treatments, several fertility preservation options were proposed. At 29 years the patient underwent laparoscopy for ovarian tissue cryopreservation. After treatments she experienced premature ovarian failure (POF) and asked for cryopreserved ovarian tissue transplantation. Before transplantation, ovarian samples were analyzed to assess neoplastic contamination and tissue quality. Two subsequent ovarian tissue transplantations were performed 4 and 7 years after cryopreservation. The follicle-stimulating hormone and luteinizing hormone reduction, estradiol increase and first menstrual cycle appeared 2 months after the second transplantation. The woman conceived spontaneously 5 months after the second transplantation. After 39 weeks of uneventful gestation, a healthy male baby was born. Ovarian tissue cryopreservation, thawing and transplantation successfully restored ovarian function and fertility after tissue storage.